Aluminum toxicity in coffee trees cultivated in nutrient solution - Pavan, M. A.; Bingham, F. T. (Pesquisa Agropecuaria Brasileira, 2014)
A solution culture experiment was designed to show the influence of low to excessive concentrations of Al on coffee yields. The treatments consisted of six Al concentrations: 0.0, 0.074, 0.148, 0.296, 0.444, and 0.888 mmol dm-3. Shoot, root and coffee fruit weights were progressively decreased under the Al treatments. There was significant reduction in all growth parameters even at lowest Al treatment. The lateral roots of Al stressed plants were thicker, shorter, and fewer in number than those of the control plants. The development of root tip was inhibited and the roots developed a brown color. The younger leaves of Al stressed plants were small, chlorotic, and curled along the margins. Aluminum toxicity symptoms on older leaves include marginal chlorosis which progressed to the center of leaf. Visual injury symptoms exhibited by coffee leaves were associated with leaf Al concentration above 300 µg g-1. Aluminum toxicity was associated with reduced uptake of Ca, Mg and P, and increased uptake of K and Al.